A systematic review of BIM usage for life cycle impact assessment. Issue 4 (23rd June 2020) - Crippa, Julianna; Araujo, Aline M.F.; Bem, Diogo; Ugaya, Cássia M.L.; Scheer, Sergio
Abstract : Purpose: This paper searches for integration methods proposed by different authors that assess the life cycle of a building using models of building information modeling (BIM) and it also compares and discusses them. Design/methodology/approach: Systematic literature review (SLR) is selected as the main research method of the present paper, aiming to collect and critically analyze multiple research studies. This paper is not only limited to studies where the whole life cycle has been assessed but also includes other papers which only integrated BIM to analyze carbon footprint, embodied carbon dioxide (CO2 ) or energy consumption. Findings: Taking into account the countries that have published articles about the subject, it is possible to deduce that it has been studied in all of the continents, except Africa. In comparison with other continents, Asia and Europe have developed more studies. Furthermore, 76% of the 34 selected articles were published in journals and only 24% in conferences proceedings, and the number of papers that relates life cycle assessment (LCA) methods using BIM has grown from 2013 to 2015, proving that the current theme is relevant. Several aspects of this literature review show the need to develop automated processes for LCA of buildings during the project's development phase. There is already a tendency to compare LCA results for buildings applied to BIM models, contributing to decision-making related to alternate projects, selection of materials, suppliers and components from an environmental perspective. Originality/value: In the current global scenario, it is the notorious negative impact on the environment over the years caused by the architecture, engineering and construction industry (AEC). The integration of BIM–LCA can reduce time and improve the application of environmental analysis. Moreover, the proper application of a LCA method to evaluate the environmental impacts of the project can be hindered due to lack of information in the database about the materials or due to failures in the interoperability between BIM software and the LCA tool.